ANALISIS IMPLEMENTASI GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA PEGAWAI PASCA NEW NORMAL PADA KANTOR KEPALA DESA SEKECAMATAN AEK NATAS KABUPATEN LABUHANBATU UTARA - Novita Laila Adetia Ritonga,; Ade Parlaungan Nasution,; Pristiyono, (JOEL: Journal of Educational and Language Research, 2022)
The purpose of this study was to determine how much influence the leadership style has on the morale of the Kantor Kepala Desa Sekecamatan Aek Natas Kabupaten Labuhanbatu Utara. The test technique used in this research is a data instrument technique test, namely data analysis with Crossloading and Boostraping Smart Pls and the method used is quantitative descriptive analysis. The population and samples used were 102 people. The data sources used are primary and secondary data which were tested with Smart Pls. Taken together, there are only two variables that have an influence on employee morale. In this study, the participatory and achievement-oriented variables have a major influence on the morale of the employees of the Kantor Kepala Desa Sekecamatan Aek Natas Kabupaten Labuhan Batu Utara